UKRAINE ON THE POLITICAL CARD OF EUROPE OF THE FIRST FOURTH OF XVII CENTURY - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article highlights the political factors that determine Ukraine’s place on the political map of Europe the first quarter of the XVII century.